ASSESSING THE RELATIONSHIP BETWEEN PERCEIVED RESTORATIVENESS AND PSYCHOLOGICAL WELLBEING AMONG STUDENTS - Nurul Ain Nabilla; Samsilah Roslan; Zeinab Ghiami; Noorlila Ahmad (Malaysian Journal of Public Health Medicine, 2018)
The purpose of this paper was to identify theories that underpin the relationship between perceived restorativeness and psychological wellbeing. This study also aimed to identify the types of activities that the respondent preferred to use as psychological resources when dealing with threatening situation. The instruments used in this study were Perceived Restorativeness for Activities Scale (PRAS) and Psychological Wellbeing Scale. The questionnaires were administered to a sample of 192 Master of Education students. The findings demonstrated that Master of Education students possess a high level of psychological well-being (Mean = 4.39, SD = 0.611) and high level of perceived restorativeness for their preferred activities (Mean = 4.57, SD = 0.76). The most preferred activities for restorativeness approach included participation in social context, followed by engaging in outdoor activities and lastly observing nature. The fascination property of perceived restorativeness obtained the highest score. Thus, the findings of the study illustrate the students’ preferred activities of restorativeness for maintaining their level of psychological wellbeing.